BUBUR KELOR SEBAGAI DIET ALTERNATIF PENDERITA DIABETES DI DESA BORISALLO KECAMATAN PARANGLOE KABUPATEN GOWA - Bahar Sinring; Suriyanti Suriyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Diabetes is a chronic disease characterized by high levels of blood sugar (glucose). If diabetes is not controlled properly, various complications can arise that endanger the sufferer's life. Blood sugar levels are controlled by the insulin hormone produced by the pancreas, an organ located behind the stomach. We are conducting a pkm on processing Moringa leaves into porridge as an alternative diet for diabetes sufferers. Considering that there are many diabetes sufferers, the combination of Moringa leaves and low-sugar rice makes it possible to make an alternative diet food for diabetes sufferers. Moringa or merunggai (moringa oleifera) is a type of plant from the moringaceae family. From the results of the nutritional content analysis, it can be seen that Moringa leaves have excellent potential to complement the nutritional needs of the body. This pkm can help diabetes sufferers find alternatives for their diet menu.